Exploring the relationship between spirituality and work values amongst hospitality students / Rahmat Hashim, Alina Shuhaida Mohd Ramly and Zulhan Othman - Hashim, Rahmat; Mohd Ramly, Alina Shuhaida; Othman, Zulhan (Faculty of Hotel and Tourism Management, Universiti Teknologi MARA, Selangor, Puncak Alam Campus, 2009)
Recent attention to issues of holistic wholeness among employees has ignited great concern about the relevancy of traditional management thinking. It has been argued that this thinking is not sufficient to address current and future concerns about effective business practice based on values, motivation and ethics in management practices. In today’s business environment where more time is spent in the workplace, understanding spirituality and work values could provide a better picture of how educational institutions could best prepare future managers. The hospitality work environment requires individuals who are “people people’. The core of this ‘people people’ lies in work and spiritual values. Hospitality school graduates entering the world of work lacking these values will not perform as expected and will be unable to develop their future professional role. Hence, hospitality management schools should be more than places for academic development, and hospitality schools should develop not only academic competence, but also a student’s self-concept. This paper reports on the investigation into the relationship between levels of spirituality and work values in the career choices of students enrolled in hotel, culinary arts and foodservice programmes. The relationship between Spirituality and Work (intrinsic) Values was found to be r = .42, significant at .001 level (highest was Awareness of Life and Creativity, r = .56, significant at .01 level). However, the findings revealed no significant association between gender, spirituality and work values.